Critical success factors to a fusion within accounting education - Norli Ali, Rozainun Abdul Aziz, Indra Devi Kandasamy,; Emmarelda, Zuraeda Ibrahim, (Opción, 2019)
The aim of this study is to offer insights for the purposes of looking into possibilities of fusion within the landscape of accounting education in Malaysia. A modified model to the current Comprehensive Accounting Education Alignment Framework is examined to consider various elements influencing accounting education development in Malaysia. A qualitative approach in methodology is adopted with views collected from various stakeholders. Results indicated some perception relating to processes. It should be noted that preference is on employer-centric requirements to match teaching and learning. It is hoped that this study has shared some insights into accounting education for all stakeholders.